Penerapan Viral marketing @tic.bandung Menggunakan Fitur User Generated Content di Instagram - Ridha, Muhammad Rasyid (Tourism and Hospitality Essentials Journal, 2021)
This research aims to investigate whether the Tourism Information Center (TIC) utilizes viral marketing methods to recommend Bandung city tourism on the Instagram account @tic.bandung. The research adopts a qualitative content analysis approach, focusing on the Instagram account @tic.bandung managed by the TIC of the Department of Culture and Tourism of Bandung City. Data for the study were collected from the content of @tic.bandung on Instagram during the year 2022, as well as through interviews with various stakeholders. The findings reveal that @tic.bandung has a clear strategy in actively engaging with its audience on Instagram by providing valuable information about tourism, hotels, and culinary experiences in Bandung. The research sheds light on TIC Bandung's efforts to employ viral marketing strategies on Instagram to enhance public awareness of their role as a tourism information source for Bandung